Evaluación del peróxido de hidrógeno en la disminución de PCBs en suelos del taller de transformadores de CNEL Manabí - Manta - Tello Sasahuay, Israel Steven (2023)
The purpose of this work was to evaluate the concentration of Hydrogen Peroxide in soils contaminated with PCBs from the CNEL EP transformer workshop in Manta city. Initially, to determine the current situation, the physical and chemical characteristics of the soil were analyzed, obtaining a resistance of 1.49 N, porosity 4.66%, pH 7.93, real density 0.95 g/cm3, apparent density 0.91 g. /cm3 and PCBs 0.12 mg/kg. Under a completely randomized design, three treatments were applied with 4 repetitions for each one; T1=20% H2O2, T2= 30% H2O2 and T3= 40% H2O2 using 100 ml of oxidant for 4 days and 10 g of ferrous sulfate heptahydrate (FeSO47H2O) was obtained as a catalyst. The statistical results complied with the normality and homoscedasticity of variance tests, demonstrating by means of the Tukey test at 5% error that there was no significant difference between the parameters, however, in T3 it presented a statistically significant difference ( sig= 0.000) in the PCBs variable, placing T3 in the first subset with an average of 0.24289 mg/kg, with a 51% reduction in the PCBs contaminant, complying with table 2 of annex 2 of Ministerial Agreement 097-A of the Regulations Environmental of Ecuador. Finally, a Guide for the management of polychlorinated biphenyls PCBs in the company CNEL EP was prepared and socialized with the workers.